DEFENSE ELEMENTS ANALYSIS IN BASKETBALL APPLIED BY WELL-KNOWN COACHES - Naid Kadušić; Zrna Agačević; Alem Kukić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
This article describes how to create a man to man defense, how to train it and how to perform a man to man defense from a 2-3 zone defense. Creating a man to man defense is commonly mistaken for oponent press tactics. Coaches tend to devote less attention to defense tactics creation, which can be main weakness in a team. It is important for a team that a coach is aware of the training techniques in order to explain them and present in proper manner. Once player comprehends the training techniques, the period of training comes, which includes helping out at every moment, as well as taking the responsibility. Match outcome and play realization provide a great insight into the players' game understanding.